Boas práticas científicas em pesquisa e bolsa de estudos - Banda, Enric (Boletim Técnico do PPEC, 2017)
Good scientific practice in research and scholarship is essential for the integrityof science. It sets internationally valid benchmarks for quality assurance, which enable replication and further studies by other scientists. And it provides safeguards against scientific dishonesty and fraud. Good practice, thus, nurtures trust within the scientific community and between science and society, both of which are necessary for scientific advance.